natural spring waters. - Pérez, Fernando (Geographicalia, 2016)
This paper analyses the incidence of forest fires in the western Pyrinees of Huesca between 1985 and 1994, its causes and interannual distribution. The high frequency rate, specially during the dried seasons, its spatial distribution and number of burnt hectares caused by rays are the most significant results of the study.
Keywords: Forest fires; ray; negligence; interannual variabiliy.